Water Quality and Pollution Index in Grenjeng River, Boyolali Regency, Indonesia - Widodo, Tatag; Budiastuti, Maria Theresia Sri; Komariah, Komariah (Caraka Tani: Journal of Sustainable Agriculture, 2019)
Grenjeng River is one of the irrigation water resources which is currently polluted by waste from industrial, livestock and domestic activities. This study aims to assess the quality and index of water pollution based on physical-chemical and biological parameters in the Grenjeng River, Boyolali Regency. Sampling of river water was carried out in dry and rainy seasons which were taken at three observation stations (upstream, middle stream and downstream). Results from laboratory analysis were compared with water quality standards according to Government Regulation No.82/2001, and quality status was based on the Pollution Index method in accordance with the attachment to Minister of Environment Decree No.115/2003. This study shows that BOD of 53-5.7 mg L-1, COD of 49-510.5 mg L-1 and total coliforms of 540-2,400,000 mLin dry season have exceeded the quality standard water classes, while in rainy season total coliforms 24,000-240,000 mLhave exceeded the standard water for all water classes. The pollution index of the river water in dry season has reached polluted to extremely polluted levels and the index of the river water in rainy season has reached moderately polluted to polluted levels. This condition shows that the practice of dumping waste into river bodies can directly affect river water quality. The irrigation water source for agricultural must comply with irrigation water quality standards so that is suitable as irrigation water for plants. Environmentally friendly approach is needed to prevent worse pollution, which is done by increasing public awareness and business actors in managing liquid waste by making the integrated wastewater treatment system.